People With Cerebral Palsy: Effects of and Perspectives for Therapy - Margaret J. Mayston (Neural Plasticity)
The movement disorder of cerebral palsy (CP) is expressed in a variety of ways and to varying degrees in each individual. The condition has become more complex over the last 20 years with the increasing survival of children born at less than 28 to 30 weeks gestationai age. Impairments present in children with CP as a direct result of the brain injury or occurring indirectly to compensate for underlying problems include abnormal muscle tone; weakness and lack of fitness; limited variety of muscle synergies; contracture and altered biomechanics, the net result being limited functional ability. Other contributors to the motor disorder include sensory, cognitive and perceptual impairments. In recent years understanding of the motor problem has increased, but less is known about effects of therapy. Evidence suggests that therapy can improve functional possibilities for children with cerebral palsy but is inconclusive as to which approach might be most beneficial. The therapist requires an understanding of the interaction of all systems, cognitive/perceptual, motor, musculoskeletal, sensory and behavioral, in the context of the development and plasticity of the CNS. It is necessary to understand the limitations of the damaged immature nervous system, but important to optimize the child's functional possibilities.